Performance of LiCoO2-coated NiO cathode under pressurized conditions - Han, J; Kim, SG; Yoon, SP; Nam, SW; Lim, TH; Oh, IH; Hong, SA; Lim, HC (ELSEVIER, 2002)
The properties of LiCoO2-coated NiO cathodes prepared by the solution impregnation technique were investigated. The electrode performance of the LiCoO2-coated cathodes were comparable with that of the conventional NiO cathode at 1, 3, and 5 atm and the prepared cathodes showed no performance decay at least for the first 1000 h at pressurized conditions. The post-analysis revealed that the LiCoO2-coated cathodes were effective in suppressing NiO dissolution up to 51% at 1 atm and 50% at 3 atm. However, the suppression of the NiO dissolution was found to be much less effective (about 11% of suppression) at 5 atm. The number of impregnations applied, in other words, the amount of LiCoO2 incorporated into the NiO cathode seemed to have no significant effect on suppressing the NiO dissolution. The Ni contents in the matrix after the 1000 h operations did not vary with increasing the LiCoO2 amount in the NiO cathodes from 0.25-0.8 mol%. In the cell with the co-flow configuration, the highest Ni content in the matrix was found at the gas inlet side and the Ni content in the matrix decreased along the gas flow direction. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: MOLTEN; SOLUBILITY